The contribution of services liberalization to poverty reduction: What role for the GATS? - Rudolf Adlung (World Trade Organization (WTO), 2007)
There are various conceivable links between services liberalization and poverty reduction, including the efficiency effects associated with increased competition in intermediate (infrastructural) services, income transfers generated by workers moving abroad, or the mobilization of private investment for social policy purposes. Arguably the most promising option for interested governments, regardless of complementary moves by trading partners, is the opening of, and creation of favourable investment conditions in, core infrastructural services. However, apart from basic telecommunications, both the Uruguay Round schedules and the offers submitted in the Doha Round to date have remained disappointing in this respect. Effective services liberalization, as measured by the share of phase-in commitments in total commitments, has occurred mainly in the context of WTO accessions and Preferential Trade Agreements. Given the apparent lack of political impetus in broader-based trade rounds, this article discusses options, in particular from the viewpoint of smaller and poorer participants, how the submission of more meaningful offers could be encouraged.
Keywords: 330; Internationaler Dienstleistungsverkehr; Außenhandelsliberalisierung; GATS; Armut